Teacher Education New Perspectives - Kayapinar, Ulas (IntechOpen, 2021)
Teacher education is an increasingly complex and challenging area of research and practice ultimately vital for generations. This book imparts insight and directions for both research and practice in teacher education. Chapters cover a variety of topics, such as collaborative teaching experiences, creativity education in curricula, innovations in science and technology in education, new techniques for learning and teaching subjects such as entrepreneurship, history, mathematics, science, technology, heritage, and early childhood education, and using online social platforms in education.